PEMBENTUKAN MODEL ARIMA UNTUK PERAMALAN INFLASI KELOMPOK BAHAN MAKANAN DI KOTA TERNATE - Rizal Rahman H Teapon (Universitas Negeri Medan, 2015)
ARIMA modeling and forecasting inflation foodstuffs in Ternate city is the purpose of this study. The method used in this research is ARIMA (Auto Regressive Moving avarage). The results showed that ARIMA (6,1,6) is the best model because it has been qualified in the test parameter estimation, diagnostic test/evaluation models and instrument evaluation test for fault models.